Preparation and properties of porous gels from poly(l‐lactic acid) and poly(d‐lactic acid) with ionic liquids as solvents and porogens. Issue 7 (21st August 2018) - Li, Lu; Li, Huaxiao; Yan, Bin; Yu, Shitao; Ge, Xiaoping
ABSTRACT: We prepared poly(lactic acid) (PLA) porous gel materials by combining poly(l ‐lactic acid) and poly(d ‐lactic acid) of three different molecular weights in different mass ratios. Moreover, we used several imidazole‐based ionic liquids with different anions as solvents and porogens at room temperature to prepare these materials. The properties of the resulting products were compared with those of materials prepared by sodium chloride as a conventional porogen and 1, 4‐dioxane as a solvent. The internal morphologies of the different types of materials were observed via scanning electron microscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis, and wettability analysis. The presented results should provide guidance and reference values for the preparation of PLA materials and for the improvement of their mechanical properties. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47058. Abstract :